Unlocking the Potential of Ketamine: A Systematic Review and Meta-analysis of its Safety and Efficacy in Acute Pain Management - Chou, Xiaojuan; Zha, Wenhua; Hu, Jian; Chen, Chen; Singh, Rajesh K.; Liu, Geng (Combinatorial Chemistry & High Throughput Screening, 2025)
IntroductionEffective acute pain management in emergency departments (ED) remains a clinical priority. Ketamine, with its analgesic properties, is being evaluated as a potential alternative to opioids due to its rapid onset and distinct mechanism of action.ObjectiveThis meta-analysis assessed the efficacy and safety of ketamine in adult ED patients with acute pain, compared to morphine, other opioids, or placebo.MethodsOnly randomized controlled trials (RCTs) comparing ketamine with opioids or placebo were included. The primary outcome was pain reduction measured using the numeric rating scale (NRS), and adverse events were evaluated as a safety endpoint. Data were analyzed using the Review Manager software. Pain scores at 10, 15, 30, and 60 minutes post-administration were compared between ketamine and control groups.ResultsNo significant differences in NRS pain scores were observed at 10 minutes [-0.46 (95% CI: -2.03, 1.10)], 30 minutes [-0.13 (95% CI: -0.62, 0.37)], or 60 minutes [-0.18 (95% CI: -0.97, 0.61)]. However, a statistically significant pain reduction was seen at 15 minutes in the ketamine group [-4.11 (95% CI: -7.91, -0.31)]. Adverse events showed no significant difference between groups [Risk Ratio: 1.20 (95% CI: 0.93, 1.55)]. High heterogeneity was noted (I2 statistics).DiscussionWhile ketamine may offer rapid analgesia at 15 minutes, its effects at other time points are comparable to controls. Safety profiles between groups were similar.ConclusionKetamine appears to be a safe alternative for acute pain relief in ED settings, with more RCTs needed to confirm time-specific efficacy.
Keywords: ketamine